2002
DOI: 10.1007/s00424-001-0751-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of KCNQ1/KCNE1 K+ channels in intestine and pancreas: lessons from the KCNE1 knockout mouse

Abstract: KCNE1 (IsK, minK) co-assembles with KCNQ1 (KvLQT1) to form voltage-dependent K(+) channels. Both KCNQ1 and KCNE1 are expressed in epithelial cells of gut and exocrine pancreas. We examined the role of KCNQ1/KCNE1 in Cl(-) secretion in small and large intestine and exocrine pancreas using the KCNE1 knockout mouse. Immunofluorescence revealed a similar basolateral localization of KCNQ1 in jejunum and colon of KCNE1 wild-type and knockout mice. Electrogenic Cl(-) secretion in the colon was not affected by gene di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 40 publications
4
52
1
Order By: Relevance
“…1A-F, in pancreas, KCNQ1 antibodies not only strongly labeled acinar cells in a similar pattern as described before 20 but also yielded good staining in insulin-positive cells, indicating the expression of KCNQ1 protein in pancreatic b-cells. In intestine (Fig.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…1A-F, in pancreas, KCNQ1 antibodies not only strongly labeled acinar cells in a similar pattern as described before 20 but also yielded good staining in insulin-positive cells, indicating the expression of KCNQ1 protein in pancreatic b-cells. In intestine (Fig.…”
Section: Resultssupporting
confidence: 78%
“…19,20,26,27 By several GWA studies, KCNQ1 has been identified as a transethnic susceptibility gene for T2D. 6 Genetic variation in KCNQ1 appears to be associated with impaired insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In the pancreas, KCNQ1 is co-expressed with products of other regulators, such as KCNE1, which may alter both its biophysical characteristics and its role. 25 As such, it is plausible that polymorphisms within the KCNQ1 gene alter the properties and role of the I KS K + channel, causing decreased pancreatic b cell function and insulin production, KCNQ1 genetic variants predict future T2DM Se Eun Park et al eventually leading to hyperglycemia. Although the function of KCNQ1 in the pancreatic b cell is not fully understood, several discrepancies have been noted about the relationship between the KCNQ1 variants and pancreatic b cell function.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that specific potassium conductance-mediated contraction is unique for the intestinal tract at least at early stages of development. In the same line, Kcnh2 seems to be the prominent pore-forming subunit expressed in the developing gut, whereas in the adult intestinal epithelia Kcnq1 is widely documented (Delomombe et al, 2001;Warth et al, 2002). This discrepancy might be due to progressive shift in the potassium modulation requirements of the developing intestinal epithelial as maturation processes.…”
Section: K Channel Pore-forming Subunits In Developing Digestive Systemmentioning
confidence: 99%